Pushing the Limits: Reining in Ohio's Residency Restrictions for Sex Offenders - Shattuck, Taurean J. (2017)
The danger to children posed by convicted sex offenders living near schools, parks, and bus stops has been greatly exaggerated by the media. In turn, many state legislatures have attempted to find solutions to this perceived problem, imposing sanctions that seem to keep the problem at bay. A relatively new approach prevents those convicted of sex crimes from living within a certain distance of places where children congregate. Ohio is one of the states that has adopted this approach. The problem with this approach, however, is that imposing such restrictions on all individuals convicted of certain crimes imposes barriers to treatment and arguably infringes upon their constitutional rights, while the efficacy of the sanctions is not backed by research data. Despite the lack of empirical support, legislatures have continued to enact tougher new laws on sex offenders. If the Ohio legislature really wanted to effectuate their goal of protecting children from dangerous sex offenders, it would allow the courts to decide on a case-by-case basis whether residency restrictions would be proper. This is an approach taken by a growing number of states that takes into account research findings on sex offenders and recidivism, as well as addresses some of the constitutional concerns of the offenders. This Note argues for this policy shift in Ohio by examining the current approach and how the issue is evolving throughout the country